Efforts to Increase Early Childhood Learning Motivation Through Structuring The Play Environment - Chusnarin Haryanti, Heny; Aryani, Rita (Kirana Publisher (KNPub), 2024)
This study aims to describe the process and results of learning through structuring the play environment that can increase learning motivation for children aged 5-6 years at Taman Kanak-Kanak B Miftahussalam, Bekasi. The research subjects consisted of 15 children, and this study used a qualitative approach with data collection techniques including observation, interviews, and documentation. The results of initial observations showed that children's learning motivation was still low, characterized by a lack of enthusiasm, active involvement, and curiosity during the learning process. Through the arrangement of a more interesting and interactive play environment, it is expected to create a pleasant learning atmosphere and encourage children to more actively participate in learning activities. This study uses the Kemmis and Taggart model of classroom action research design, which includes planning, action, observation, and reflection stages. The results showed an increase in children's learning motivation after the arrangement of the play environment was carried out, with children becoming more excited, enthusiastic, and actively asking questions. The implications of this study emphasize the importance of structuring the play environment in the early childhood learning process, which can have a positive impact on their learning motivation. This research is expected to make a positive contribution to the development of more effective learning methods in early childhood education and become a reference for teachers and future researchers.